Maintenance of leptospira species in leptospira Vanaporn Wuthiekanun agar. - Wuthiekanun, V; Amornchai, P; Langla, S; Oyuchua, M; Day, N; Limmathurotsakul, D (American Society for Microbiology, 2014)
The maintenance of Leptospira species in liquid or semisolid medium is time-consuming and at risk of contamination due to the needs of routine subculture and dark field microscopy. Using Leptospira Vanaporn Wuthiekanun (LVW) agar, we maintained 100 pathogenic Leptospira isolates for 12 months without the need for subculture and confirmed the viability of all isolates by the naked eye.